Cybersecurity, race, and the politics of truth. (August 2022) - Whyte, Jeffrey
This article explores the racial politics underwriting cybersecurity's recent human turn toward the issues of online disinformation and 'foreign influence' in US politics. Through a case study of the Black Lives Matter (BLM) movement, this article's first half considers how contemporary cybersecurity has produced 'racial division' as an object of security by framing the BLM movement as a geopolitical vulnerability open to foreign manipulation through social media. In its emphasis on the political protest as a site of insecurity, I argue that contemporary cybersecurity has widened its traditional spatiality 'beyond the computer'. In the article's second half, I argue that the racialization of cybersecurity has underwritten a politics of truth ultimately concerned less with parsing true from false, and more with defining the boundaries of secure political knowledge and communication. I argue that contemporary cybersecurity has produced an idealized subject for whom an obligation to possess contingent forms of knowledge becomes a condition of secure political subjectivity. I conclude with a critique of contemporary cybersecurity's tendency to portray dissident political movements like BLM as ignorant or disinformed.